Optic nerve tissue displacement during mild intraocular pressure elevation: its relationship to central corneal thickness and corneal hysteresis. (19th June 2018) - Bedggood, Phillip; Tanabe, Fumi; McKendrick, Allison M.; Turpin, Andrew; Anderson, Andrew J.; Bui, Bang V.
Abstract: Purpose: To determine the extent to which (1) optic nerve tissue is displaced following mild acute elevation of intraocular pressure, and (2) clinically accessible measures at the anterior eye can be used as a surrogate for such displacements. Methods: We imaged the optic disc of 21 healthy subjects before and after intraocular pressure (IOP) elevation of ~10 mmHg delivered by ophthalmodynamometry. Steady‐state tissue displacement during IOP elevation was assessed axially from OCT data, and laterally from SLO data. Recovery from IOP elevation was assessed by tracking a single vertical B‐scan through the cup centre. Anatomical structures were demarcated by three masked clinicians to determine lateral shifts for temporal cup edge and central disc vessels, and axial shifts of disc surface and anterior lamina cribrosa. Spatial maps of deformation were constructed within the demarcated cup and disc to assess within‐tissue displacement. Measured displacements were correlated with corneal hysteresis, corneal thickness, and IOP. Results: The temporal cup edge moved more temporally with higher baseline IOP ( R 2  = 0.33, p  = 0.006) and with lesser elevation of IOP ( R 2  = 0.43, p  = 0.001); it moved more superiorly for thinner corneas ( R 2  = 0.35, p  = 0.007). Thinner corneas also produced less within‐cup deformation, relative to that of the disc ( R 2  = 0.39, p  = 0.004). Axial displacement of the lamina and lateral displacement of vessels were often substantial (lamina 20 ± 15 μm, range 1–60 μm; vessels 37 ± 25 μm, range 2–102 μm) but did not correlate with measured parameters. Recovery from IOP elevation did not take more than 300–400 ms in any subject. Conclusions: Mild acute elevation of IOP produces large and rapidly reversible shifts in optic nerve tissue in young, healthy eyes. The resulting degree, direction and spatial distribution of cup movement are associated with IOP status and corneal thickness, but not corneal hysteresis.